Inserção, atuação e ascensão profissional: o papel do capital social em usinas sucroalcooleiras do interior paulista - Cenedezi-Zanarotti, Vanessa Regina (2012)
From the financial logic that changes the investment outlook favoring capital dispersion and fragmentation of control of the business, many industries and businesses have been directly affected by the entry of new capital. In several cases the entry of new capital is not restricted to purely investment of resources, but influence the management of companies, for example, prioritizing the adoption of Corporate Governance as a necessary instrument to regulate the relations among more actors. As a result of these new practices, values, structures and culture are modified starting to integrate new models of standardization of organizational action. Through research conducted in the field in two sugarcane industries, one of family fully control and another of mixed control, aimed from the analysis of the results pertaining to two specific organizational actions: professionalization and dispersion of capital verify the value of the Social Capital in organizational environments surveyed focusing on the importance of this concept in the processes of insertion, performance and career advancement. In the surveyed companies, strong correlations were observed between new organizational processes and revaluation of Social Capital contradicting the initial expectations that the professionalization and dispersion of capital could undermine its importance. Moreover, the concept also showed his productive character in relation to the processes of insertion, performance and career advancement valuing the importance of it in the sugar and alcohol sector. Although the Social Capital is present in both surveyed professional environments, is apprehended differently in the two companies.